Concomitant Temozolomide Plus Radiotherapy Demonstrates Favorable Progression Free Survival in Recurrent Meningioma. (16th November 2020) - Belanger, Katherine; Ung, Timothy H; Ney, Douglas; Lillehei, Kevin O; Rusthoven, Chad; Damek, Denise M; Ormond, David R
Abstract: INTRODUCTION: Malignant and recurrent meningiomas are often treatment resistant and remain a therapeutic challenge. Radiation therapy (RT) is a mainstay of treatment with limited systemic options for patients after local treatment failure. Improving the efficacy of RT may be beneficial in this setting. Temozolomide (TMZ) is a DNA alkylating agent that appears to have a synergistic effect with radiation therapy in gliomas and may be worthwhile as a radiosensitizing agent when given concomitantly with radiation for meningiomas. METHODS: We performed a retrospective analysis of patients with meningioma treated at the University of Colorado with concomitant TMZ chemoradiation either as adjuvant treatment after surgical excision or as primary therapy at tumor recurrence. Progression free survival and meningioma specific survival were calculated from the start of concomitant treatment to local recurrence or meningioma-related death, respectively. RESULTS: Eleven patients (12 tumors) were treated with concomitant TMZ chemoradiation with a median follow-up of 41.5 months. There were two WHO Grade I, eight WHO Grade II and two WHO Grade III meningiomas. Three of 11 patients died during the follow-up period; one being disease related (11.1%). Two patients had meningioma recurrence during the follow-up period, one with a WHO Grade III meningioma at 2.3 months, and one additional patient at 5.4 years (WHO grade II). Six-month PFS was 91.7%, with 83.3% remaining without recurrence at last follow-up. CONCLUSION: Treatment options are quite limited for meningiomas after local failure. In this study, concomitant TMZ chemoradiation improved progression free survival in the treatment of malignant and recurrent meningiomas in comparison to historic controls. While only a small series, further study is warranted to find novel methods to prevent local failure after RT for the treatment of malignant and recurrent meningiomas.